2020
DOI: 10.1177/0972150920923316
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Forecasting for Airline Industry: The Case of Indian Air Passenger and Air Cargo

Abstract: This study aims to forecast air passenger and cargo demand of the Indian aviation industry using the autoregressive integrated moving average (ARIMA) and Bayesian structural time series (BSTS) models. We utilized 10 years’ (2009–2018) air passenger and cargo data obtained from the Directorate General of Civil Aviation (DGCA-India) website. The study assessed both ARIMA and BSTS models’ ability to incorporate uncertainty under dynamic settings. Findings inferred that, along with ARIMA, BSTS is also suitable for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Madhavan et al [69] attempted to forecast aviation demand throughput in the Indian aviation industry. The bayesian structural time series (BSTS) approach is used.…”
Section: Tablementioning
confidence: 99%
“…Madhavan et al [69] attempted to forecast aviation demand throughput in the Indian aviation industry. The bayesian structural time series (BSTS) approach is used.…”
Section: Tablementioning
confidence: 99%
“…This method was implemented to air travel passenger demand and it was shown that the proposed method outperforms other common methods in terms of forecasting passenger traffic. Madhavan et al 23 used ARIMA and Bayesian Structural Time Series (BSTS) models to forecast the air passenger and cargo demand of the Indian aviation industry. According to the findings, it was concluded that the BSTS approach, together with ARIMA, is also suitable for short‐term forecasting of international passenger, domestic passenger, international air cargo and domestic air cargo.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are several approaches for predicting data. To maintain a large variation in prediction and forecasting, the normalization method is required to make them closer [21]. Standard deviation can still be used with normalised data because both translation and linear scaling have no effect on it.…”
Section: Normalization 431 Normalize Datamentioning
confidence: 99%